Linguistic study of the text of Uzbek folk epics (Global Scientific Review, 2025)
This article examines the linguistic study of the text of Uzbek folk oral epics. It also contains information on dialects, lexical-semantic and functional-stylistic features, frequency dictionary, lexicographic research, explanatory dictionary, descriptive-descriptive, artistic-aesthetic function of language units, and authorial lexicography